2014
DOI: 10.33073/pjm-2014-038
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microsatellite-Primed PCR (MSP-PCR) and PCR Melting Profile (PCR-MP) Method for Intraspecies Differentiation of Dermatophytes

Abstract: In this study, two PCR-based methods (MSP-PCR and PCR-MP) were compared for their abilities to identify intraspecies variations of 23 isolates of Trichophyton rubrum, 78 isolates of Trichophyton interdigitale and 22 isolates of Microsporum canis, obtained mainly from patients in Lódź city. The results allowed to distinguish four types (containing two subtypes) characteristic for T. interdigitale and three types characteristic for T. rubrum using PCR-MP method. Analysis conducted using MSP-PCR with (GACA)4 prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…These techniques can also help to characterize infecting strains and monitor their occurrence and distribution [31]. Moreover, the most important investigation in the molecular epidemiology of dermatophytes is to determine whether infections are caused by the same or different strains [51]. In this aspect, disclosure of infection sources and transmission pathways in populations of humans and animals is necessary, and available techniques should allow deep genetic differentiation of strains within species, thus facilitating prompt and reliable identification of individual clones [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques can also help to characterize infecting strains and monitor their occurrence and distribution [31]. Moreover, the most important investigation in the molecular epidemiology of dermatophytes is to determine whether infections are caused by the same or different strains [51]. In this aspect, disclosure of infection sources and transmission pathways in populations of humans and animals is necessary, and available techniques should allow deep genetic differentiation of strains within species, thus facilitating prompt and reliable identification of individual clones [52].…”
Section: Discussionmentioning
confidence: 99%
“…Our investigation showed a relatively high genomic diversity revealed by the MP-PCR analysis of clinical isolates of T. mentagrophytes of both human and animal origin. Although the MP-PCR method is widely described in the literature as a useful tool for the epidemiological analysis of the source of infection [31,49,51,53], it seems that it cannot be used to detect recalcitrant to treatment dermatophyte isolates. The molecular basis of terbinafine resistance is most widely described to result mostly from changes at the genome level [18,27,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated the application of the PCR melting profile as a simple method that may be used for intraspecies differentiation of analysed strains of A. keratinophilus isolated from pellets of Corvus frugilegus . This method has been successfully used for distinguishing bacterial strains such as S. aureus or E. coli 42 and for differentiation of dermatophytes 18 , 43 . We chose the Bam HI restriction enzyme and an appropriate denaturation temperature to obtain high differentiation power with the PCR-MP method.…”
Section: Discussionmentioning
confidence: 99%
“…After onychomycosis , which, by far, is the most difficult to cure, and tinea capitis , the most prevalent superficial mycosis in the United States and Canada is tinea pedis (affecting approximately 40% of the population), followed by tinea corporis and tinea cruris 5 , 6 . Therefore, fungal skin infections, including those caused by dermatophytes, are now referred to as civilization diseases, which are a significant public health problem 7 9 .…”
Section: Introductionmentioning
confidence: 99%